Food insecurity among low-income households in Addis Ababa, Ethiopia - Tefera Darge Delbiso; Fekadu Mulugeta Asfaw; Tibebu Moges; Debebe Ero; Messay Gebremariam Kotecho (Heliyon, 2024)
With the rapid urbanization in developing countries, poverty and food insecurity are becoming increasing prevalent, posing a major challenge to urban areas. The COVID-19 pandemic induced job losses and reduced income combined with inflation have further exacerbated the household food insecurity situation, particularly in cities of low-income countries. Our study aims to assess the extent of food insecurity and its determinants among low-income household in Addis Ababa, Ethiopia. We conducted a community-based cross-sectional study among a sample of 578 households in Addis Ababa. We estimated the household food insecurity status using the Household Food Insecurity Access Scale (HFIAS). An ordinal logistic regression model was used to assess the relationship between household food insecurity status and the socioeconomic and demographic covariates. The STATA 14 software package was used for data analysis. We found that household food insecurity was prevalent among low-income households in Addis Ababa, with a prevalence rate of 92.4 % (95 % CI: 90.2–94.6 %). Of these households, 33.6 % (95 % CI: 29.7–37.4 %) were severely food insecure. To cope with the food shortage, households were forced to reduce their food quantity and quality. We also found that respondent's education, engagement in income generating activities, and household wealth were independently associated with household food insecurity. We conclude that although supporting people living below the poverty line (pro-poor) remains the top priority for social protection programs, adapting the program to accommodate the working poor (informal sector employees and casual workers) is crucial, especially during shocks.